Analysis of the Effect of Welding Sequence Variations on Residual Stresses and Distortions for Welding Pressure Vessels Structures at PT. Petrokimia Gresik using the Finite Element Method - Nur Syahroni; Bayu Iman Fatkurokhim; Handayanu Handayanu (International Journal of Offshore and Coastal Engineering (IJOCE), 2017)
The development of oil and gas industry technology has been very advanced, one of the implementation is to connect material materials to support oil and gas industry facilities. Residual stress may occur due to high temperature differences due to welding and also uneven heat distribution. This causes the material to become hard but brittle so that it may cause structural failure in the connection area. In this final project will be simulated welding pressure vessels to determine the structure of residual stresses that occur as well as the influence of Post Weld Heat Treatment on residual stress itself. The material used is aluminum and WPS data coming from the fabrication company. The simulation is divided into 2 steps: thermal and structural analysis. The value of the residual voltage of 1 to pathline pathline 3 is 189 MPa, 124.8 MPa, 100.76 MPa with distortion value of 40.43 mm. Then analyzed Post Weld Heat Treatment referring to AWS D1.1: 2000 to reduce residual stresses that occur. From the results of the Post Weld Heat Treatment value of the residual stress can be reduced significantly. After being treated Post Weld Heat Treatment with variations of temperatures of 200 C, 300 C The maximum residual voltage reduction occurs in pathline 1 to pathline 3 at 125 MPa, 93 MPa, 100 MPa.